Pengujian Kandungan Informasi Arus Kas Dan Laba Akuntansi Terhadap Return Saham: Studi Pada Perusahaan LQ45 - Samsul Hadi; Syahril Djaddang; Suyanto (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2017)
This study aimed to analyze the effect of changes in cash flow from operating activities, cash flows from investing avtivities, cash flow from financing activities and accounting earnings on stock returns in the Indonesian capital market. Research conducted on 15 companies listed in the LQ45 index in the Indonesia Stock Exchange (BEI). Observations were made for 4 years from 2011 to 2014. Data were analyzed using data panel analysis. The results show that operating cash flow and financing cash flow significantly influence stock returns. This means any increase in operating cash flow and in expenditures for financing activities followed by an increase in stock returns. Accounting earnings and cash flows have no significant effect on stock returns, since the accounting information and investment cash flows of the sample companies do not contain relevant information and market anomalies occur due to investor failure to understand accrual information, cash flow, market risk and conservatism.